EFSUMB 2020 Proposal for a Contrast-Enhanced Ultrasound-Adapted Bosniak Cyst Categorization – Position Statement - Cantisani, Vito; Bertolotto, Michele; Clevert, Dirk-André; Correas, Jean-Michel; Drudi, Francesco Maria; Fischer, Thomas; Gilja, Odd Helge; Granata, Antonio; Graumann, Ole; Harvey, Christopher J.; Ignee, Andre; Jenssen, Christian; Lerchbaumer, Markus Herbert; Ragel, Matthew; Saftoiu, Adrian; Serra, Andreas L.; Stock, Konrad Friedrich; Webb, Jolanta; Sidhu, Paul S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
The well-established Bosniak renal cyst classification is based on contrast-enhanced computed tomography determining the malignant potential of cystic renal lesions. Ultrasound has not been incorporated into this pathway. However, the development of ultrasound contrast agents coupled with the superior resolution of ultrasound makes it possible to redefine the imaging of cystic renal lesions. In this position statement, an EFSUMB Expert Task Force reviews, analyzes, and describes the accumulated knowledge and limitations and presents the current position on the use of ultrasound contrast agents in the evaluation of cystic renal lesions.
Keywords: urinary tract; renal cyst; Bosniak classification; CEUS; cystic renal lesions